Characterization at Atomic Resolution of Carbon Nanotube/Resin Interface in Nanocomposites by Mapping sp2-Bonding States Using Electron Energy-Loss Spectroscopy. (22nd June 2016) - Su, Yi-Feng; Park, Jin G.; Koo, Ana; Trayner, Sarah; Hao, Ayou; Downes, Rebekah; Liang, Richard
Abstract: Functionalization is critical for improving mechanical properties of carbon nanotubes (CNTs)/polymer nanocomposites. A fundamental understanding of the role of the CNT/polymer interface and bonding structure is key to improving functionalization procedures for higher mechanical performance. In this study, we investigated the effects of chemical functionalization on the nanocomposite interface at atomic resolution to provide direct and quantifiable information of the interactions and interface formation between CNT surfaces and adjacent resin molecules. We observed and compared electronic structures and their changes at the interfaces of nonfunctionalized and functionalized CNT/polymer nanocomposite samples via scanning transmission electron microscopy and electron energy-loss spectroscopy (EELS) spectrum imaging techniques. The results show that the state of sp 2 bonding and its distribution at the CNT/resin interface can be clearly visualized through EELS mapping. We found that the functionalized CNT/polymer samples exhibited a lower fraction of sp 2 bonding and a lower π*/σ* ratio compared with the nonfunctionalized cases. A good correlation between near-edge fine structures and low-loss plasmon energies was observed.